Assessment of the strength of recommendation and quality of evidence: GRADE checklist. A descriptive study - Bezerra, Camila Torres; Grande, Antonio José; Galvão, Vivianny Kelly; Santos, Douglas Henrique Marin dos; Atallah, Álvaro Nagib; Silva, Valter (São Paulo Medical Journal, 2022)
BACKGROUND: Grading of Recommendations Assessment, Development and Evaluation (GRADE) is a tool for assessing evidence produced in synthesis reports. OBJECTIVES: To present the translation into Portuguese of the GRADE checklist, whose original version is in English, and to describe and explain each topic, in order to provide examples to researchers and professionals who will use the tool. DESIGN AND SETTING: Descriptive study developed at Centro Universitário Tiradentes, Maceió, Alagoas, Brazil.METHODS: This was a translation of the GRADE checklist, with the addition of the Risk Of Bias In Systematic Reviews (ROBIS) tool in the checklist, with examples of its use.RESULTS: Situations of practical use of the tool were presented in order to facilitate and expand the use of assessment of the quality and strength of evidence among Portuguese speakers. CONCLUSIONS: The GRADE checklist is valuable in helping to assess the strength and quality of evidence for synthesis reports for healthcare decision-making.